2020
DOI: 10.3390/ijerph17030958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Financial Crisis on Socioeconomic Inequalities in Mortality in Small Areas in Seven Spanish Cities

Abstract: Background: The aim of this study was to analyze the trend in socioeconomic inequalities in mortality in small areas due to several specific causes before (2001–2004, 2005–2008) and during (2009–2012) the economic crisis in seven Spanish cities. Methods: This ecological study of trends, with census tracts as the areas of analysis, was based on three periods. Several causes of death were studied. A socioeconomic deprivation index was calculated for each census tract. For each small area, we estimated standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Focusing on the financial crisis effects, we found only one study providing findings about the crisis impact on regional variation in suicide from Spain, which found a maximum gap between regions of about 55-65% [27]. Another study exploring the crisis effects on the variation between seven Spanish cities reported elevated suicide rates associated with crisis in three cities, and no effect in four cities [30]. There is evidence from previous research [31] that social and economic transition may not be uniform, with some regions affected much more than others.…”
Section: Discussionmentioning
confidence: 82%
“…Focusing on the financial crisis effects, we found only one study providing findings about the crisis impact on regional variation in suicide from Spain, which found a maximum gap between regions of about 55-65% [27]. Another study exploring the crisis effects on the variation between seven Spanish cities reported elevated suicide rates associated with crisis in three cities, and no effect in four cities [30]. There is evidence from previous research [31] that social and economic transition may not be uniform, with some regions affected much more than others.…”
Section: Discussionmentioning
confidence: 82%
“…Differences in mortality rates between districts are linked to many urban phenomena; cities are composed of areas with considerable environmental and social heterogeneity, including serious poverty and very substandard living conditions that are associated with disease, mortality, and substandard levels of health. For example, the impact of the last financial crisis on mortality rates by socio-economic inequalities in small areas in Spain was analysed in a recent paper [27].…”
Section: Discussionmentioning
confidence: 99%
“…Within this growing scientific interest, various studies have investigated the impact of the economic slowdown on the population’s health and healthcare, both in Spain [ 14 , 15 , 16 ] and in other European countries [ 7 , 17 , 18 , 19 ], as well as in other continents [ 20 , 21 ]. The 2008 economic crisis coincided with the implementation of austerity policies that reduced the capacity of the Spanish public health system.…”
Section: Introductionmentioning
confidence: 99%